Analisis Determinan Indeks Pembangunan Manusia Di Padang Lawas Utara - Hasibuan, Faizah; Yusrizal, Yusrizal; Harahap, Muhammad Ikhsan (ITB AAS INDONESIA Surakarta, 2024)
The Human Development Index (HDI) is an indicator to measure the quality of human life that aims to achieve the level of public welfare. The HDI has three elements, namely health, education achieved, and a decent standard of living in terms of the economy. In increasing the Human Development Index (HDI) can be achieved by increasing education, health, and income. The income in question is per capita income, and to support education and health in order to continue to increase, a budget issued by the government is needed. This study uses quantitative methods and data processed using Eviews 12 with technical data analysis using Vector Error Correction Model (VECM) analysis. The results of this study indicate that the variable per capita income (X1) in the long term has a significant negative effect on the Human Development Index (Y) and the magnitude of its influence is 27.1%. The Education Budget variable (X2) in the long run has a significant positive effect on the Human Development Index variable (Y) and the effect is 12.4%. And the Health Budget variable (X3) in the short term has a significant positive effect on the Human Development Index variable (Y) and the effect on the Y variable is 1.6%.